Indonesian EFL Teachers' Views on Implementing Genre-Based Approach for Reading Classes in Junior High Schools: A Qualitative Study - Nina Puspitaloka; Khofifatul Nur Kholifah (Borneo Educational Journal (Borju), 2025)
English as a Foreign Language (EFL) education in Indonesia has grown in importance as a result of the global demand for English competence. Reading comprehension in junior high school is an important part of language development and academic accomplishment. This qualitative case study looks into the use of the Genre-Based Approach (GBA) in reading instruction at a public junior high school in Karawang, Indonesia. The study investigates how GBA helps students grasp different text genres and how teachers adjust this technique to meet classroom demands. Data were gathered through classroom observations in a Grade VII English class, as well as semi-structured interviews with one English teacher. Thematic analysis was performed to discover repeating patterns and contextual elements that affect GBA implementation. Findings show that teachers possess a solid understanding of GBA stages and apply them using curriculum-aligned materials such as English for Nusantara text book. The approach enhances students’ comprehension of text structure, communicative purpose, and critical thinking. However, challenges remain, including limited instructional time, varied student proficiency, and appropriate text selection.